An in-situ formed bifunctional layer for suppressing Li dendrite growth and stabilizing the solid electrolyte interphase layer of anode free lithium metal batteries. (10th December 2022) - Merso, Semaw Kebede; Tekaligne, Teshager Mekonnen; Weldeyohannes, Haile Hisho; Nikodimos, Yosef; Shitaw, Kassie Nigus; Jiang, Shi-Kai; Huang, Chen-Jui; Wondimkun, Zewdu Tadesse; Jote, Bikila Alemu; Wichmann, Lennart; Brunklaus, Gunther; Winter, Martin; et al.
Abstract: Anode-free lithium metal batteries (AFLMBs) can achieve a high energy density. However, achieving high-capacity retention and Coulombic efficiency (CE) are challenging without a continuous Li supply from the Cu anode side. The lower CE and rapid capacity decay in AFLMBs are primarily due to non-uniform Li deposition and electrolyte decomposition during cycling. Herein, strontium fluoride (SrF2 ) nanoparticles are applied on Cu foils to attain the in-situ forming of a bifunctional interfacial layer, a Li-Sr alloy, and a LiF-rich SEI composite layer during Li plating. The derived Cu@SrF2 electrode has excellent plating/stripping stability and outstanding performance. AFLMB full cell (Cu@SrF2 //NCM111) attains an average Coulombic efficiency (ACE) of 98.6 % and capacity retention of 51.0 % at the 60 th cycle using a commercial carbonate-based electrolyte. In contrast, the bare AFLMB full cell (BCu//NCM111) only has an ACE of 94.9 % with a capacity retention of 10.2 % under the same conditions. The concept is proven in lithium metal batteries (LMBs). This strategy provides a simultaneous Li nucleation and formation of LiF-rich SEI layers, rendering it promising to realize AFLMBs and LMBs with long lifespans and high CE. Graphical abstract: Unlabelled Image Highlights: SrF2 nanoparticles have high mechanical strength and good lithiophilic properties. Cu@SrF2 electrode shows uniform and compact Li deposition. The LiF-rich SEI and Li-Sr alloy layers give a synergy for outstanding performance. This strategy provides Li nucleation and the formation of LiF-rich SEI layers. The approach enables for realizing of AFLMBs and LMBs with long lifespans.